Mapping the Landscape, Influence, and Publication Visibility of Activity-Based Costing (ABC) and Activity-Based Management (ABM): A Comprehensive Bibliometric Analysis - Rizky Nuryanti; Syafrozi Haqi; Nurika Restuningdiah; Puji Handayati (International Forum of Researchers and Lecturers, 2025)
As business complexity and global competition intensify, the limitations of traditional cost accounting systems in providing relevant information for strategic decision-making become increasingly apparent. This has driven the adoption of Activity-Based Costing (ABC) and subsequently Activity-Based Management (ABM), which have evolved as vital tools to accurately allocate costs based on activities and transform this information into value-enhancing and efficiency-improving strategies. This study aims to map the landscape, influence, and visibility of ABC and ABM publications through a comprehensive bibliometric analysis using VOSviewer. The research method involves a Systematic Literature Review (SLR) for data collection and screening from 488 publications (2023-2025) indexed in Scopus from Google Scholar, followed by data analysis and visualization of co-authorship and keyword co-occurrence networks. The analysis results show the dominance of core concepts such as